Multiscale study on the compressive performance of diverse solid waste backfill bodies - Hang Yin; Jiepeng Liu; Xuhong Zhou; Hongtuo Qi; Shuxian Liu; Shuai Pang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract To create green, low-energy self-compacting backfill materials, this study utilizes aeolian sand, slag, red mud, and calcium carbide slag to prepare diverse solid waste backfill materials in synergy. Additionally, a suitable amount of polypropylene fibers is added to enhance its toughness. During the experimental process, unconfined compressive strength tests were conducted using digital speckle technique. Computerized tomography scanning technology was employed for internal 3D visualization of the samples. Material strength difference mechanisms were characterized using SEM–EDS and XRD microscopic techniques. Finally, discrete element numerical simulation was utilized for analyzing the evolution of sample failure. The results show that with the increase in calcium carbide slag doping, the specimen UCS increases and then decreases, and when the doping of calcium carbide slag is 14%, the specimen UCS reaches a local maximum of 3.552 MPa; with the increase in the water–solid ratio, the specimen UCS gradually decreases, and when the water–solid ratio is 0.3, the specimen UCS reaches a local minimum of 3.26 MPa. With the increase in calcium slag doping, the mass percentage of calcium element and calcium-silicon ratio in the multi-solid waste matrix first increased and then decreased, and the micro-morphology of the multi-solid waste matrix included lamellar, block, and rod structures; With the increase in the water–solid ratio, the micro-morphology of the multi-solid waste matrix was gradually transformed, and the pore defects between the cementitious materials gradually increased. With the increase in calcium carbide slag doping, the porosity within the unit decreases, and when the doping of calcium carbide slag exceeds 14%, the porosity increases and the compressive strength decreases; with the gradual increase in the water–solid ratio, the porosity within the unit gradually increases, and the number of holes in the specimen reaches a minimum of 208 within the range of the study when the water–solid ratio is 0.24. Digital speckle technique and PFC numerical simulation together elucidate the sample’s failure process and crack evolution mechanism. Initially, the internal voids of the sample are gradually compacted, and crack propagation is slow. As the load increases to the peak, localized deformation and macroscopic crack formation occur in the sample. After the peak load, the sample exhibits significant displacement deformation, and the number of cracks increases significantly. The research findings can provide reference for the design and construction of solid waste backfill pipelines and trenches.